GERAKAN PERILAKU CERDIK PENCEGAHAN PENYAKIT GAGAL GINJAL DAN PERAWATAN HEMODIALISA - Roifah, Ifa; Nur Soemah, Sri Sudarsih & Agus Hermansyah, Eka (JURNAL KEPERAWATAN BINA SEHAT, 2018)
Kidney failure is one type of chronic disease that has gone through certain stages. In the early stages usually kidney failure begins with a lack of kidney function. Maybe the kidneys only reduce their function by about 20 percent. However, because it is not considered, the kidneys that are less functioning can cause damage up to 80 percent. This condition is called kidney failure. Hemodialysis is one of the best interventions for patients with acute kidney failure or terminal kidney failure who experience fluid imbalances. The phenomenon that often occurs is the lack of public knowledge about the prevention of kidney failure and the lack of ability of post hemodialysis patients and families to deal with problems that are often felt by patients after undergoing hemodialysis. Counseling about early prevention of kidney failure and post-hemodialysis treatment at home is an alternative in helping people and patients and their families to reduce ignorance and disability. The stages of the activities that have been carried out in the community service activities are preparing the material to be delivered at the time of counseling and coordinating with the Sakinah Hospital, especially with experts on hemodialysis and nutritionists in the Sakinah Hospital. Next is to make an animated video that is used for counseling about the smart behavior movement to prevent kidney failure and hemodialysis treatment. The results obtained from the animation service community service activities are very effective to improve public understanding of the clever behavior of prevention of kidney failure and hemodialysis treatment.